1982
DOI: 10.1080/00224498209551131
|View full text |Cite
|
Sign up to set email alerts
|

Equity and sexual satisfaction in recently married couples

Abstract: This study was designed to determine whether or not equity considerations are important in couples' sexual relations. To answer this question, 53 newlywed couples were interviewed about their sexual relationships. Two main hypotheses were tested: (a) Men and women who feel their relationships are equitable will be more content (less distressed) than people who feel either overbenefited or underbenefited. (b) Men and women who feel equitably treated will have more satisfying sexual relations than those who feel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 4 publications
2
37
0
1
Order By: Relevance
“…This finding is important in light of previous research that demonstrated that spouse support is important for marital satisfaction (Hatfield et al, 1982;Pasch & Bradbury, 1998) and parent-child involvement (Belsky, 1990;Belsky et al, 1991;Ehrenberg et al, 2001). Full-time employed mothers reported more emotional support from spouses than did at-home mothers, and this may be a result of the overlap of worker-parent identities shared by employed mothers and fathers.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…This finding is important in light of previous research that demonstrated that spouse support is important for marital satisfaction (Hatfield et al, 1982;Pasch & Bradbury, 1998) and parent-child involvement (Belsky, 1990;Belsky et al, 1991;Ehrenberg et al, 2001). Full-time employed mothers reported more emotional support from spouses than did at-home mothers, and this may be a result of the overlap of worker-parent identities shared by employed mothers and fathers.…”
Section: Discussionmentioning
confidence: 46%
“…There is also considerable evidence that perceived spousal social support is greatest in equitable marital relationships (Deutsch, 1999;Risman & Johnson-Sumerford, 1998;Van Willigen & Drentea, 2001). Other researchers have concluded that nonequitable relationships are more likely to be associated with increased depression (Glass & Fujimoto, 1994;Mirowsky, 1985;Schafer & Keith, 1980), decreased marital satisfaction (Hatfield, Greenberger, Traupmann, & Lambert, 1982), and reports of decreased marital quality (Pina & Bengston, 1993).…”
mentioning
confidence: 98%
“…Las mujeres mostraron una asociación significativa entre este esquema y la satisfacción sexual. Según la psicología social, la satisfacción sexual depende en gran medida de los constructos culturales, morales y éticos de los individuos, y la mujer occidental es criticada por mantener abiertamente relaciones sexuales 12,28,29 .…”
Section: Discussionunclassified
“…Hatfield, Greenberger, Traupmann and Lambert (1982) found that newlywed couples who were equitably treated, were more content and less distressed than those who were over or under benefited. Equitable couples also had more satisfying sexual relationships.…”
Section: Social Exchange Theorymentioning
confidence: 99%